Effect of Teaching Behaviour Change in Secondary Level Education Children: A Comprehensive Review - Ghimire, Mayanath; Bhattarai, Tikaram; Dahal, Shanta Bahadur; Dahal, Ram Kumar; Kunmar, Jayram (GS WOW: Wisdom of Worthy Research Journal, 2025)
To explore effectiveness of the learning behaviour in Secondary level of children in Nepal. This research adopted the process of scientific review as Meta synthesis to get solution of effectiveness of the learning behaviour in secondary level of children in Nepal as pragmatic research philosophy. The researcher attempts In-depth archival analysis followed by an intensive review would be strategies adopted during the scientific review. Depending on the nature of the availability of data, qualitative and quantitative research approaches would be effective. The review was systematically conducted through the collection of research papers along with reports and data’s. Student conduct influences community perception, teacher effectiveness and wellbeing, as well as the academic success of all students. When students are involved, they learn more, which has the greatest effect on student learning. Instruction is required to cultivate 21st century student skills, including in-depth mastery of challenging material, critical thinking, complex problem-solving, effective communication and collaboration, and self-directed learning. Student conduct influences community perception, teacher effectiveness and wellbeing, as well as the academic success of all students. When students are involved, they learn more, which has the greatest effect on student learning.